2018
DOI: 10.1002/ece3.3913
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the natural regeneration of the pioneering shrub Calligonum mongolicum in sand dune stabilization plantations in arid deserts of northwest China

Abstract: Calligonum mongolicum is a successful pioneer shrub to combat desertification, which is widely used for vegetation restoration in the desert regions of northwest China. In order to reveal the limitations to natural regeneration of C. mongolicum by asexual and sexual reproduction, following the process of sand dune stabilization, we assessed clonal shoots, seedling emergence, soil seed bank density, and soil physical characteristics in mobile and stabilized sand dunes. Controlled field and pot experiments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…Higher sand content in upper soil layers in arid zones is also linked to more stable soil‐moisture dynamics (Zhang & Shao ). Remnant soils had higher surface compaction than expected, which may increase evaporative water loss from the compacted soil surface and inhibit seedling establishment (Fan et al ). Higher surface compaction in remnant soils may represent degradation from drought, the trampling effects from wildlife or, conversely, natural hydrological processes of surface soils to enhance water run‐off toward vegetated patches (Tongway & Ludwig ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher sand content in upper soil layers in arid zones is also linked to more stable soil‐moisture dynamics (Zhang & Shao ). Remnant soils had higher surface compaction than expected, which may increase evaporative water loss from the compacted soil surface and inhibit seedling establishment (Fan et al ). Higher surface compaction in remnant soils may represent degradation from drought, the trampling effects from wildlife or, conversely, natural hydrological processes of surface soils to enhance water run‐off toward vegetated patches (Tongway & Ludwig ).…”
Section: Discussionmentioning
confidence: 99%
“…arborescens and C. rubicundum (Feng et al 2008;Fan et al 2018), which could be related to the aforementioned traits.…”
Section: Discussionmentioning
confidence: 99%
“…Calligonum mongolicum shrubs are simultaneously and quite often exposed to wind erosion and sand burial, but serve well as a pioneer species in the Minqin deserts ( Fan et al, 2018 ). In this study, we investigated the effects of burial depth, seed age, and light intensity on the seedling emergence of C. mongolicum , and found that the species in seedling emergence stage are well adapted to sand, and have a procreation bet-hedging strategy to adapt to the extreme environment stresses in the desert.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it remains unknown which strategy was adopted by pioneer shrubs to inhabit mobile sand dunes and to adapt to unpredictable sand movement and extreme drought. Calligonum mongolicum (Polygonaceae) is a dominant native perennial shrub in active sand dunes in arid deserts of northern China, and is widely used for vegetation restoration in desert region ( Fan et al, 2018 ). In these sandy habitats, each mature shrub produces numerous quantities of fruit and seeds are dispersed considerable distances by prevailing winds.…”
Section: Introductionmentioning
confidence: 99%